Room-temperature quantum nanoplasmonic coherent perfect absorption - Lai, Yiming; Clarke, Daniel D. A.; Grimm, Philipp; Devi, Asha; Wigger, Daniel; Helbig, Tobias; Hofmann, Tobias; Thomale, Ronny; Huang, Jer-Shing; Hecht, Bert; Hess, Ortwin (Nature communications, 2024)
Light-matter superposition states obtained via strong coupling play a decisive role in quantum information processing, but the deleterious effects of material dissipation and environment-induced decoherence inevitably destroy coherent light-matter polaritons over time. Here, we propose the use of coherent perfect absorption under near-field driving to prepare and protect the polaritonic states of a single quantum emitter interacting with a plasmonic nanocavity at room temperature. Our scheme of quantum nanoplasmonic coherent perfect absorption leverages an inherent frequency specificity to selectively initialize the coupled system in a chosen plasmon-emitter dressed state, while the coherent, unidirectional and non-perturbing near-field energy transfer from a proximal plasmonic waveguide can in principle render the dressed state robust against dynamic dissipation under ambient conditions. Our study establishes a previously unexplored paradigm for quantum state preparation and coherence preservation in plasmonic cavity quantum electrodynamics, offering compelling prospects for elevating quantum nanophotonic technologies to ambient temperatures. Quantum states are incredibly sensitive to their environment, making them perfect for ultrasensitive quantum detection—if they can be maintained long enough. Here, the authors showed that they can ‘immortalize’ the excited state of a coupled light-matter system using a technique called ‘coherent perfect absorption’.